2007
DOI: 10.1097/01.mlr.0000259879.05499.eb
|View full text |Cite
|
Sign up to set email alerts
|

Practical Issues in the Application of Item Response Theory

Abstract: This article describes CCFA methods for checking IRT model assumptions and provides suggestions for using these methods in practice. It offers insight into ways information gained through IRT can be applied to evaluate items and aid in scale construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…Our finding that an IRT-based CAT can result in accurate assessments with far less items than tests based on traditional psychometrics is fully comparable to findings in other studies, applying IRT CAT techniques in the fields of intelligence and school achievement assessment, [16,17] and in the field of Quality of Life [18,22,47]. The first studies on the application of IRT models in the field of the identification of behavioural and emotional problems in paediatric care have now been published, [19-22] and these studies came to similar conclusions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that an IRT-based CAT can result in accurate assessments with far less items than tests based on traditional psychometrics is fully comparable to findings in other studies, applying IRT CAT techniques in the fields of intelligence and school achievement assessment, [16,17] and in the field of Quality of Life [18,22,47]. The first studies on the application of IRT models in the field of the identification of behavioural and emotional problems in paediatric care have now been published, [19-22] and these studies came to similar conclusions.…”
Section: Discussionsupporting
confidence: 88%
“…This led to IRT-based test procedures in the field of quality of life measurements [18]. Some publications have been published describing the application of these models to the assessment of mental health problems [19-22]. …”
Section: Introductionmentioning
confidence: 99%
“…However, our findings indicated that the presence of multidimensionality has not affected the result of the DIF analysis. One possible explanation, based on the results of CFA analysis (not shown here), might be that the residual correlations and modification indices [43] implied not only similar secondary dimensions on both social and school subscales for father and mother groups, but also no mean difference in the secondary traits. In this regard, Oshima and Miller [40] showed that multidimensional items are not necessarily biased unless there is a mean difference in the secondary trait.…”
Section: Discussionmentioning
confidence: 88%
“…8,9 Indeed, CAT allows for the administration of only the items that will offer the most relevance for a given individual, reducing the length of the questionnaire and the completion time in addition to maintaining the test's precision. 1012 Additionally, multidimensional CAT (MCAT) based on multidimensional IRT (MIRT) has been recently applied to measure health problems in various chronic diseases (e.g., symptomatology, fatigue, physical, and emotional functioning). 1318 Because of the multidimensional nature of QoL, this method seems relevant in developing a valid and reliable adaptive short-form QoL questionnaire.…”
Section: Introductionmentioning
confidence: 99%